Optimization of Photovoltaic Electrolyzer Hybrid systems; taking into account the effect of climate conditions. (15th June 2016) - Sayedin, Farid; Maroufmashat, Azadeh; Sattari, Sourena; Elkamel, Ali; Fowler, Michael
Highlights: The optimal size of directly coupled Photovoltaic–Electrolyzer (PV/EL) is studied. The effect of climate condition on the performance of PV/EL is studied. PV/EL energy transfer loss and the levelized cost of hydrogen production minimized. The model is applied to locations with different climate and solar irradiations. Solar to electricity/electricity to hydrogen/solar to hydrogen efficiencies are derived. Abstract: Solar energy will make a valuable contribution for power generation in the future. However the intermittency of solar energy has become an important issue in the utilization of PV system, especially small scale distributed solar energy conversion systems. The issue can be addressed through the management of production and storage of the energy in the form of hydrogen. The hydrogen can be produced by solar photovoltaic (PV) powered electrolysis of water. The amount of transferred energy to an electrolyzer from a PV module is a function of the distance between maximum power points (MPP) of PV module and the electrolyzer operating points. The distance can be minimized by optimizing the number of series and parallel units of the electrolyzer. However the maximum power points are subject to PV module characteristics, solar irradiation and ambient temperature. This means the climate condition can substantially influence the MPP and therefore the optimal size of the PV–Electrolyzer (PV/EL) system. On the other hand, system size can affect the levelized cost of hydrogen production as well. In this paper, the impact of climate conditions on the optimal size and operating conditions of a direct coupled photovoltaic–electrolyzer system has been studied. For this purpose, the optimal size of electrolyzer for six cities which have different climate condition is obtained by considering two solution scenarios, regarding two objectives which are annual energy transfer loss and levelized costs of hydrogen production and then the optimal results for these cities are compared. The results show that the climate condition can strongly affect the size of the electrolyzer, the annual hydrogen production and consequently, both the levelized costs of hydrogen production and annual energy transfer loss. Moreover, it is found out that the solar to hydrogen efficiency of the optimal systems regarding these cities are different based on the solution scenarios, the characteristics of PV output power and the configuration of optimal electrolyzer configuration and placement.